Batteries containing β-delithiated layered nickel oxide electrochemically active cathode materials
By using non-stoichiometric β-delithable layered nickel oxide and treating it through alkali metal hydroxide, a specific layered structure is formed, the problem of high-oxidation transition metal oxides in the battery is solved, and the performance of the battery is improved. stability.
Patent Information
- Application Number
- CN202210855678.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-05-09
- Filing Date
- 2018-05-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2038-05-08
AI Technical Summary
When high-oxidation transition metal oxides in existing batteries are used as electrochemically active cathode materials, they are prone to gas precipitation, structural integrity problems, cathode swelling and thermodynamic instability, limiting the improvement of battery performance.
Using non-stoichiometric β-delithable layered nickel oxide as the electrochemically active cathode material, the stacking of O1-type layer and γ-hydroxynickel oxide sample layer is formed by alkali metal hydroxide treatment. The structure of the structure reduces the oxygen evolution rate and self-discharge, and improves capacity maintenance.
It significantly reduces the oxygen evolution rate and self-discharge, improves the battery's discharge capacity maintenance and open circuit voltage, and enhances the battery's low, medium and high discharge rate performance.
Smart Images

Figure CN115231630B_ABST
Abstract
Description
[0001] This application is a divisional application of the following application: Application date: May 18, 2018; Application number: 201880030824X; Invention name: "Battery containing β-delithiated layered nickel oxide electrochemically active cathode material".
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit under 35 USC §119(e) of U.S. Provisional Patent Application No. 62 / 503,829, filed May 9, 2017, the entire disclosure of which is incorporated herein by reference. Technical Field
[0004] The present invention relates to electrochemically active cathode materials, and more particularly, to non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode materials and batteries containing the same. Background Art
[0005] Electrochemical cells or batteries are commonly used as a source of electrical energy. The battery contains a negative electrode, commonly called an anode, and a positive electrode, commonly called a cathode. The anode contains an electrochemically active anode material that can be oxidized. The cathode contains an electrochemically active cathode material that can be reduced. The electrochemically active anode material is capable of reducing the electrochemically active cathode material. A separator is disposed between the anode and the cathode. An ionically conductive electrolyte solution is in intimate contact with the cathode, anode and separator. The battery components are disposed in a can or housing, which is usually made of metal.
[0006] When using a battery as an electrical energy source in an electronic device, the anode and cathode are brought into electrical contact, allowing electrons to flow through the device and allowing the corresponding oxidation and reduction reactions to occur to provide electrical energy for the electronic device. The electrolyte is in contact with the anode, cathode and separator. The electrolyte contains ions that flow through the separator between the anode and cathode to maintain charge balance throughout the battery during discharge.
[0007] There is an increasing need to create batteries that are better suited for powering modern electronic devices such as toys; remote controls; audio equipment; flashlights; digital cameras and peripheral photography devices; electronic games; toothbrushes; radios; and clocks. To meet this need, batteries may contain higher loadings of electrochemically active anode and / or cathode materials to provide increased capacity and service life. However, batteries have common sizes, such as AA, AAA, AAAA, C, and D cell sizes, which have fixed outer dimensions and constrained internal volumes. This limits the ability to achieve better performing batteries by simply increasing the loading of electrochemically active materials.
[0008] The battery's electrochemically active cathode material is another design feature that can be adjusted to provide higher performance. For example, electrochemically active materials with higher volumetric and gravimetric capacities can produce better performing batteries. Similarly, electrochemically active materials with higher oxidation states can also produce better performing batteries. However, the electrochemically active material selected must provide an acceptable closed circuit voltage, or operating voltage range, for the device that the battery may power. If the battery's open circuit voltage (OCV) or operating voltage is too high, the device may be damaged. Conversely, if the battery's operating voltage is too low, the device may not operate at all.
[0009] In addition, electrochemically active cathode materials such as high oxidation state transition metal oxides may be highly reactive. When such an electrochemically active cathode material is introduced into a battery and it is in contact with an electrolyte solution, the high reactivity of the electrochemically active cathode material may lead to the precipitation of gas. Any gas precipitated may lead to an increase in pressure in the battery, resulting in structural integrity problems, such as continuity in the cathode and / or leakage of electrolyte from the battery. High oxidation state transition metal oxides may also react harmfully with other battery components such as conductive carbon additives such as graphite, other additives such as one or more surfactants, and / or diaphragms. High oxidation state transition metal oxides may also have a tendency to react with electrolytes, which may cause other structural problems in the battery, such as cathode swelling, and water consumption, which in turn may lead to unfavorable water balance in the battery. In addition, when the battery is stored for a long time, a battery containing high oxidation state transition metal oxides as an electrochemically active cathode material may, for example, exhibit thermodynamic instability and exhibit an increase in self-discharge rate. In addition, it is necessary to properly balance the ratio of the content of both water and potassium hydroxide in the battery to the content of the electrochemically active material to maximize the use of these two electrochemically active electrode materials. Furthermore, selecting an appropriate ratio of both water and potassium hydroxide content to the electrochemically active material content can provide enhanced cell performance over a variety of discharge rate regimes.
[0010] It would be desirable to provide an electrochemically active cathode material for use in a battery that meets the needs discussed above. The non-stoichiometric, beta-delithiated layered nickel oxide electrochemically active cathode material of the present invention particularly meets these needs. Summary of the invention
[0011] In one embodiment, the present invention relates to a battery. The battery includes a cathode, an anode, a separator between the cathode and the anode, and an electrolyte. The cathode includes a conductive additive and an electrochemically active cathode material. The electrochemically active cathode material includes a non-stoichiometric β-delithiated layered nickel oxide. The non-stoichiometric β-delithiated layered nickel oxide has a chemical formula. The chemical formula is Li x A y Ni 1+a-z M zO2•nH2O, wherein x is from about 0.02 to about 0.20; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; and n is from about 0 to about 1. In the chemical formula, A is an alkali metal. Alkali metals include potassium, rubidium, cesium, and any combination thereof. In the chemical formula, M includes alkaline earth metals, transition metals, non-transition metals, and any combination thereof. Alkaline earth metals may include magnesium, calcium, and combinations thereof. Transition metals may include cobalt, manganese, titanium, yttrium, and combinations thereof. Non-transition metals may include aluminum, gallium, indium, germanium, tin, and any combination thereof. The anode comprises an electrochemically active anode material. Electrochemically active anode materials include zinc, zinc alloys, and any combination thereof.
[0012] In another embodiment, the present invention is directed to an electrochemically active cathode material comprising a non-stoichiometric β-delithiated layered nickel oxide having a layered crystal structure characterized by a lattice comprising multiple NiO2 layers, wherein the NiO2 lattice comprises an ordered O1-type layer stacking sequence, at least one O3-type layer stacking fault and at least one γ-nickel oxyhydroxide (γ-NiOOH)-like layer stacking fault. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] While the specification concludes with claims particularly pointing out and distinctly claiming the subject matter regarded as forming the present invention, it is believed the present invention will be better understood from the following description when read in conjunction with the accompanying drawings.
[0014] Figure 1 is a cross-section of one embodiment of a primary alkaline cell comprising a beta-delithiated layered nickel oxide electrochemically active cathode material.
[0015] Figure 2 Includes a powder X-ray diffraction pattern of stoichiometric lithium nickelate (lower figure) and a powder X-ray diffraction pattern of non-stoichiometric lithium nickelate containing excess nickel (upper figure).
[0016] Figure 3 Includes a powder X-ray diffraction pattern of stoichiometric α-delithiated layered nickel oxide (lower figure) and a powder X-ray diffraction pattern of non-stoichiometric α-delithiated layered nickel oxide (upper figure).
[0017] Figure 4 An X-ray diffraction pattern of an embodiment including non-stoichiometric β-delithiated layered nickel oxide (upper figure) and a powder X-ray diffraction pattern of γ-delithiated layered nickel oxide having a γ-NiOOH-type structure with P3-type layer stacking (lower figure).
[0018] Figure 5Schematic representations of (A) a lattice with O3-type layer stacking order, (B) a lattice with O1-type layer stacking order, and (C) a lattice with O1-type stacking order, wherein O3-type stacking faults are statistically distributed throughout the lattice.
[0019] Fig. 6A Includes high-resolution scanning transmission electron micrographs showing the presence of O3-type layer stacking faults in an ordered O1-type layer stacking sequence of nonstoichiometric β-delithiated layered nickel oxide, Figure 6B is a converged beam electron diffraction pattern showing the presence of an O3-type layer stacking fault (4.7 Å) in an ordered O1-type stacking order (7.2 Å) of one embodiment of a non-stoichiometric β-delithiated layered nickel oxide.
[0020] Figure 7 In (A) is included a powder X-ray diffraction pattern of an embodiment of β-delithiated layered nickel oxide, and in (B) is included a corresponding simulated X-ray diffraction pattern calculated by DIFFaX software, in which it is assumed that the combination of O3-type and P3-type (i.e., γ-NiOOH-type) stacking faults are statistically distributed in a lattice with an ordered O1-type layer stacking order. DETAILED DESCRIPTION
[0021] Electrochemical cells or batteries can be primary or secondary. A primary battery means that it is only discharged (e.g., to exhaustion) once and then discarded. For example, primary batteries are described in David Linden, Handbook of Batteries (4th edition, 2011). Secondary batteries mean rechargeable. Secondary batteries can be discharged and charged multiple times, for example, more than fifty times, one hundred times or more times. For example, secondary batteries are described in David Linden, Handbook of Batteries (4th edition, 2011). Accordingly, batteries may include various electrochemical pairs and electrolyte combinations. Although the description and examples provided herein are generally directed to primary alkaline electrochemical cells or batteries, it should be understood that the present invention is applicable to primary and secondary batteries with aqueous, non-aqueous, ionic liquid and solid electrolyte systems. Therefore, primary and secondary batteries including the above-mentioned electrolytes are within the scope of the present application and the present invention is not limited to any particular embodiment.
[0022] Reference Figure 1, a primary alkaline electrochemical cell or battery 10 is shown, which includes a cathode 12, an anode 14, a separator 16, and a housing 18. The battery 10 also includes a current collector 20, a seal 22, and an end cap 24. The end cap 24 serves as a negative terminal of the battery 10. A positive protrusion (pip) 26 is located at the end of the battery 10 opposite the end cap 24. The positive protrusion 26 can serve as a positive terminal of the battery 10. An electrolyte solution is dispersed throughout the battery 10. The cathode 12, the anode 14, the separator 16, the electrolyte, the current collector 20, and the seal 22 are contained within the housing 18. The battery 10 can be, for example, an alkaline battery of size AA, AAA, AAAA, C, or D.
[0023] The housing 18 can be any conventional type of housing commonly used in primary alkaline batteries and can be made of any suitable base material, such as cold rolled steel or nickel-plated cold rolled steel. The housing 18 can have a cylindrical shape. The housing 18 can be any other suitable non-cylindrical shape. The housing 18 can, for example, have a shape including at least two parallel plates, such as a rectangular, square or prismatic shape. The housing 18 can, for example, be deep drawn from a sheet of a base material such as cold rolled steel or nickel-plated steel. The housing 18 can, for example, be drawn into a cylindrical shape. The housing 18 can have at least one open end. The housing 18 can have a closed end and an open end with a side wall therebetween. The inner surface of the side wall of the housing 18 can be treated with a material that provides a low electrical contact resistance between the inner surface of the side wall of the housing 18 and an electrode such as the cathode 12. The inner surface of the side wall of the housing 18 can be plated with, for example, nickel, cobalt and / or coated with a carbonaceous coating to reduce, for example, the contact resistance between the inner surface of the side wall of the housing 18 and the cathode 12.
[0024] Cathode 12 comprises at least one electrochemically active cathode material. The electrochemically active cathode material may be a non-stoichiometric β-delithiated layered nickel oxide. The β-delithiated layered nickel oxide may have a general chemical formula Li x A y Ni 1+a-z M z O2•nH2O, wherein x is from about 0.02 to about 0.20; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; n is from about 0 to about 1; A includes alkali metals; M includes alkaline earth metals, transition metals, non-transition metals, and any combination thereof. Because a is positive, a non-stoichiometric amount of nickel (and / or other metal M) must be present in the material (i.e., an excess of nickel (and / or other metal) relative to the amount required to balance the charge of the oxygen atoms), so the β-delithiated layered nickel oxide is considered to be non-stoichiometric. The non-stoichiometric β-delithiated layered nickel oxide may have a general chemical formula Li x A y Ni 1+a-z M zO2•nH2O, wherein x is from about 0.03 to about 0.12; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; n is from about 0 to about 1; A includes alkali metals; M includes alkaline earth metals, transition metals, non-transition metals, and any combination thereof.
[0025] In embodiments of non-stoichiometric β-delithiated layered nickel oxide, x may be in the range of 0.02 to 0.2, such as 0.02 to 0.18, 0.02 to 0.16, 0.02 to 0.15, 0.03 to 0.20, 0.03 to 0.19, 0.03 to 0.15, 0.03 to 0.12, 0.05 to 0.19, or 0.05 to 0.15. In embodiments, y may be in the range of 0.03 to 0.20, such as 0.03 to 0.17, 0.03 to 0.15, 0.03 to 0.13, 0.06 to 0.20, 0.06 to 0.17, 0.06 to 0.15, 0.06 to 0.13, 0.08 to 0.17, 0.08 to 0.15, or 0.08 to 0.13. In embodiments, a may be in the range of 0.02 to 0.20, such as 0.02 to 0.18, 0.02 to 0.16, 0.03 to 0.20, 0.03 to 0.17, 0.03 to 0.15, 0.04 to 0.20, 0.04 to 0.17, 0.04 to 0.15, 0.04 to 0.13, or 0.04 to 0.11. When a is less than 0.02, it is found that the stability of non-stoichiometric β-delithiated layered nickel oxide is poor. In embodiments, z may be in the range of 0 to 0.20, such as 0.03 to 0.20 or 0.04 to 0.20. In embodiments, z may be 0. In embodiments where z is 0, a may be in the range of 0.02 to 0.20, such as 0.02 to 0.16, 0.03 to 0.15, or 0.02 to 0.15. In embodiments, the difference (az) may be in the range of 0.02 to 0.20, e.g., 0.02 to 0.16, 0.04 to 0.20, 0.04 to 0.16, 0.06 to 0.16, or 0.08 to 0.18. In embodiments, A may be potassium and y may be in the range of 0.06 to 0.14, e.g., 0.08 to 0.13. In embodiments, z is 0 and 1+(az) is greater than 1, such that Ni itself is present in a non-stoichiometric amount, e.g., 1+(az) may be in the range of about 1.02 to about 1.20.
[0026] The electrochemically active cathode material may have a weight capacity. The non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode material may have a weight capacity of greater than about 340 mAh / g or greater than about 350 mAh / g. The non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode material may have a weight capacity of about 340 mAh / g to about 400 mAh / g, about 350 mAh / g to about 400 mAh / g, about 340 mAh / g to about 380 mAh / g, or about 360 mAh / g to about 400 mAh / g.
[0027] Elements from Group 1A of the periodic table are often referred to as alkali metals. Alkali metals may include an element or any combination of elements from Group 1A of the periodic table. Alkali metals may include, for example, potassium (K), rubidium (Rb), cesium (Cs), and any combination thereof.
[0028] Elements from Group IIA of the periodic table are often referred to as alkaline earth metals. Alkaline earth metals may include any combination of elements or elements from Group IIA of the periodic table. Alkaline earth metals may include, for example, magnesium (Mg), calcium (Ca), and combinations thereof.
[0029] Elements from IB-VIIIB groups of the periodic table are generally referred to as transition metals. Transition metals may include elements from IB-VIIIB groups of the periodic table or any combination of elements. Transition metals may include, for example, cobalt (Co), manganese (Mn), yttrium (Y), titanium (Ti), zinc (Zn), and any combination thereof.
[0030] The non-transition metal may include, for example, aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn), and any combination thereof.
[0031] The alkali metal may be, for example, potassium (K). The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li x K y Ni 1+a-z M z O2•nH2O, wherein x is from about 0.02 to about 0.20; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; and n is from about 0 to about 1. The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li x K y Ni 1+a-z M zO2•nH2O, wherein x is from about 0.02 to about 0.20; y is from about 0.08 to about 0.13; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; n is from about 0 to about 1; M includes alkaline earth metals, transition metals, non-transition metals, and any combination thereof. The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li 0.13 K 0.13 Ni 1.16 O2•0.26H2O or Li 0.07 K 0.13 Ni 1.11 O2•0.53H2O.
[0032] The alkaline earth metal may be, for example, magnesium (Mg). The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li x K y Ni 1+a-z Mg z O2•nH2O, wherein x is from about 0.02 to about 0.2; y is from about 0.03 to about 0.2; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; and n is from about 0 to about 1. The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li 0.15 K 0.10 Ni 1.05 Mg 0.04 O2•0.24H2O.
[0033] The transition metal may be, for example, cobalt (Co). The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li x K y Ni 1+a-z Co z O2•nH2O, wherein x is from about 0.02 to about 0.2; y is from about 0.03 to about 0.2; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; and n is from about 0 to about 1. The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li 0.04 K 0.011 Ni 1.03 Co 0.03 O2•nH2O.
[0034] The non-transition metal may be, for example, aluminum (Al). The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li x K y Ni 1+a-z Al zO2•nH2O, wherein x is from about 0.02 to about 0.2; y is from about 0.03 to about 0.2; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; and n is from about 0 to about 1. The chemical formula of the non-stoichiometric β-delithiated layered nickel oxide may be, for example, Li 0.12 K 0.09 Ni 1.08 Al 0.02 O2•0.18H2O.
[0035] The content of the one or more alkali metals, the one or more alkaline earth metals, the one or more transition metals and / or the one or more non-transition metals in the non-stoichiometric β-delithiated layered nickel oxide can be determined by any acceptable method known in the art. For example, the content of the one or more alkali metals and the one or more transition metals in the non-stoichiometric β-delithiated layered nickel oxide can be determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and / or atomic absorption (AA) spectroscopy. ICP-AES and / or AA analysis can be performed, for example, using standard methods such as JR Dean, Practical Inductively Coupled Plasma Spectroscopy, pp. 65-87 (2005) and B. Welz and MB Sperling, Atomic Absorption Spectrometry, pp. 221-294 (3rd edition, 1999). The ICP-AES analysis of sample materials such as non-stoichiometric β-delithiated layered nickel oxide can be completed using the Ultima 2 ICP spectrometer available from HORIBA Scientific (Tokyo, Japan). ICP-AES analysis of the non-stoichiometric β-delithiated layered nickel oxide can be performed at different wavelengths, depending on the elements contained in the non-stoichiometric β-delithiated layered nickel oxide. As determined by ICP-AES, the potassium content in the non-stoichiometric β-delithiated layered nickel oxide can be less than about 7 wt %. As determined by ICP-AES, the potassium content in the non-stoichiometric β-delithiated layered nickel oxide can be about 2 wt % to about 7 wt %, or about 3 wt % to about 7 wt %.
[0036] The water content in the non-stoichiometric β-de-lithiated layered nickel oxide can be determined by any acceptable method known in the art. For example, the water content in the non-stoichiometric β-de-lithiated layered nickel oxide can be determined by thermogravimetric analysis (TGA). TGA determines, for example, the absorbed water and adsorbed water of the sample material, the water content in the lattice of the sample material, and the total water content in the sample material by measuring the change in the weight of the sample as the temperature increases. TGA is described by, for example, RF Speyer, Thermal Analysis of Materials (1994). TGA of sample materials such as non-stoichiometric β-de-lithiated layered nickel oxide can be completed using the Q5000 analyzer available from TA Instruments (Newcastle, DE, USA).
[0037] Powder X-ray diffraction (pXRD) is an analytical technique for characterizing the lattice structure of a sample material such as a crystalline powder. XRD analysis of a crystalline sample material will yield a characteristic diffraction pattern consisting of peaks of different intensities, widths, and diffraction angles (peak positions) corresponding to the diffraction planes in the crystal structure of the sample material. The XRD pattern can be measured using an X-ray diffractometer using CuKα radiation by standard methods such as BD Cullity and SR Stock, Elements of X-ray Diffraction (3rd edition, 2001). Powder XRD analysis of sample materials such as non-stoichiometric β-delithiation layered nickel oxide can be completed using a D-8 Advance X-ray diffractometer available from Bruker Corporation (Madison, WI. USA). Unit cell parameters such as unit cell length and angle of the sample material can be determined, for example, by Rietveld refinement of the XRD pattern. Rietveld refinement is described, for example, in HM Rietveld, "A Profile Refinement Method for Nuclear and Magnetic Structures", Journal of Applied Crystallography, pp. 65-71 (1969).
[0038] The crystallite size of the sample material can be determined by the peak broadening of the XRD pattern of the sample material containing a silicon (Si) standard. Peak broadening analysis can be performed, for example, by the single peak Scherrer method or the Warren-Averbach method as discussed in HP Klug and LE Alexander, "X-ray Diffraction Procedures for Polycrystalline and Amorphous Materials", Wiley, pp. 618-694 (1974). The Warren-Averbach method can also be used to determine the residual strain and stress of the sample material.
[0039] The full width at half maximum (FWHM) can be used to characterize the relative sharpness or width of lines in a diffraction pattern of a sample material. FWHM can be determined by measuring the intensity of a peak, dividing the measured intensity by 2 to calculate the half intensity (half height), and measuring the peak width at the calculated half height.
[0040] Normalized intensity, along with peak position, can be used to compare relative diffraction efficiencies associated with specific diffraction planes within the crystal lattice of a sample material. Normalized intensity can be calculated for peaks within the same XRD pattern. All peaks in an XRD pattern can be normalized based on the peak with the highest intensity (reference peak). Normalization is reported as a percentage and is performed by dividing the intensity of the normalized peak in count points by the intensity of the reference peak in count points and multiplying by 100. For example, the intensity of a reference peak may be 425, while the intensity of the normalized peak may be 106. The normalized intensity of the peak is 25%, for example [(106 / 425)•100]. The normalized intensity of the reference peak is 100%.
[0041] The obtained XRD pattern can be compared with a known XRD pattern. A comparative XRD pattern can be generated from a known sample material. In addition, the obtained XRD pattern can be compared with a known XRD pattern in, for example, a Powder Diffraction File (PDF) database available from the International Centre for Diffraction Data (Newton Square, PA, USA) or an Inorganic Crystal Structure Database (ICSD) available from FIZ Karlsruhe (Eggenstein-Leopoldshafen, Germany). Comparison with a known sample material or PDF (International center for Diffraction Data, Newton Square, PA) will determine whether the obtained XRD pattern of the sample material is completely different, similar, or identical to the known XRD pattern of the material. Known XRD patterns in the PDF database for comparison with, for example, β-delithiated layered nickel oxide include PDF #00-06-0141 for β-nickel oxyhydroxide; PDF #00-00675 for γ-nickel oxyhydroxide; PDF #00-006-0075 for nickel oxide; and PDF #00-059-0463 for β-nickel hydroxide.
[0042] The non-stoichiometric β-delithiated layered nickel oxide may have a characteristic powder X-ray diffraction pattern. Figure 4An example of an XRD pattern of non-stoichiometric β-delithiated layered nickel oxide is shown in (above). The measured XRD pattern does not correspond to any X-ray diffraction pattern reported in, for example, a PDF database. The XRD pattern may include a combination of peaks or peaks indicating β-delithiated layered nickel oxide. The XRD pattern may include characteristic FWHM values of several peaks of β-delithiated layered nickel oxide. The XRD pattern may also include characteristic normalized intensities of several peaks of non-stoichiometric β-delithiated layered nickel oxide. The XRD pattern of non-stoichiometric β-delithiated layered nickel oxide may include a first peak. The first peak may have a peak position of about 14.9°2θ to about 16.9°2θ on the XRD pattern. The first peak may be, for example, at about 15.4°2θ. The XRD pattern of non-stoichiometric β-delithiated layered nickel oxide may include a second peak. The second peak may have a peak position of about 21.3°2θ to about 22.7°2θ on the XRD pattern. The second peak may be, for example, at about 22.1°2θ. The XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may include a third peak. The third peak may have a peak position of about 37.1°2θ to about 37.4°2θ on the XRD pattern. The third peak may be, for example, at about 37.3°2θ. The XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may include a fourth peak. The fourth peak may have a peak position of about 43.2°2θ to about 44.0°2θ on the XRD pattern. The fourth peak may be, for example, at about 43.6°2θ. The XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may include a fifth peak. The fifth peak may have a peak position of about 59.6°2θ to about 60.6°2θ on the XRD pattern. The fifth peak may be, for example, at about 60.1°2θ. The XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may include a sixth peak. The sixth peak may have a peak position of about 65.4°2θ to about 65.9°2θ on the XRD spectrum. The sixth peak may be, for example, at about 65.7°2θ. The XRD spectrum of the non-stoichiometric β-delithiated layered nickel oxide may include a seventh peak. The seventh peak may have a peak position of about 10.8°2θ to about 12.0°2θ on the XRD spectrum. The seventh peak may be, for example, at about 11.2°2θ. The XRD spectrum of the non-stoichiometric β-delithiated layered nickel oxide may include an eighth peak. The eighth peak may have a peak position of about 48.1°2θ to about 48.6°2θ on the XRD spectrum. The eighth peak may be, for example, at about 48.3°2θ.
[0043] The first peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM (FWHM). The FWHM of the first peak may be about 1.01°2θ to about 2.09°2θ. The FWHM of the first peak may be, for example, about 1.37°2θ. The second peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the second peak may be about 0.86°2θ to about 1.95°2θ. The FWHM of the second peak may be, for example, about 1.37°2θ. The third peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the third peak may be about 0.23°2θ to about 0.41°2θ. The FWHM of the third peak may be, for example, about 0.28°2θ. The fourth peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the fourth peak may be about 0.40°2θ to about 0.75°2θ. The FWHM of the fourth peak may be, for example, about 0.60°2θ. The fifth peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the fifth peak may be about 0.57°2θ to about 1.45°2θ. The FWHM of the fifth peak may be, for example, about 0.92°2θ. The sixth peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the sixth peak may be about 0.27°2θ to about 0.53°2θ. The FWHM of the sixth peak may be, for example, about 0.36°2θ. The seventh peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the seventh peak may be about 0.56°2θ to about 1.73°2θ. The FWHM of the seventh peak may be, for example, about 1.13°2θ. The eighth peak of the XRD pattern of the non-stoichiometric β-delithiated layered nickel oxide may have a FWHM. The FWHM of the eighth peak may be about 0.33°2θ to about 0.58°2θ. The FWHM of the eighth peak may be, for example, about 0.45°2θ.
[0044] Several peaks in the x-ray diffraction pattern of the non-stoichiometric β-delithiated layered nickel oxide have significantly larger FWHM values than other peaks in the diffraction pattern, such as the first, second, fifth and seventh peaks. Without intending to be bound by theory, it is believed that the broadening of specific diffraction peaks in the x-ray diffraction pattern is the result of the formation of various deformation defects in the layered lattice structure, such as planar defects such as stacking faults, which can destroy the long-range layer stacking order of the NiO2 layer of the lithium nickel oxide precursor.
[0045] In the case of nominally stoichiometric lithium nickel (III) oxide LiNiO2 (i.e., lithium nickelate), the lattice symmetry is rhombohedral and the crystal structure belongs to the R-3m space group. Nominally stoichiometric lithium nickel (III) oxide (lithium nickelate) having the general formula LiNiO2 can be prepared by the procedure described by Arai et al. (Solid State Ionics 80 (1995) 261-269). Alternatively, stoichiometric lithium nickelate can be purchased from commercial sources (e.g., American Elements, Los Angeles, CA). Figure 2 Powder X-ray diffraction patterns of nominally stoichiometric lithium nickelate, whether produced by Arai or obtained commercially, are shown. The lithium nickelate lattice structure consists of stacks of NiO2 layers with triangular symmetry and cubic close packing in the oxygen sublattice. The basic building block of the NiO2 layer is the NiO6 octahedron, which shares its edges with other NiO6 octahedra located in the same layer to form an extended edge-sharing network. The lithium ions are located in octahedral positions defined by oxygen atoms in the interlayer regions between the NiO2 layers. The NiO2 layers are systematically aligned with respect to each other to form stacks of alternating NiO2 layers and lithium-containing layers with long-range order. This type of long-range order can be classified as an O3-type layer stacking order, in which the repeating unit comprises three NiO2 layers with AB CA BC oxygen stacking, such as Figure 5 As shown in A.
[0046] As the nickel (III) of the stoichiometric lithium nickelate is oxidized to nickel (IV), lithium ions will be deintercalated to maintain the overall charge electronic neutrality without eliminating oxygen from the lattice. Stoichiometric lithium nickelate can be delithiated by the general method described by Arai et al. (Electrochimica Acta50 (2005) 1821-1828). The resulting delithiated layered nickel oxide containing Ni (IV) is referred to as α-delithiated layered nickel oxide in this article, and almost all lithium ions are removed from the interlayer region, usually leaving only about 5% to 10% of lithium (based on the total lithium in the lithium nickelate precursor). As lithium ions are removed from the interlayer of lithium nickelate, NiO2 layers can more easily slide relative to each other and form different stacking sequences with lower energy to minimize the electrostatic repulsion between the nickel ions and oxygen ions in the relative NiO2 layers. Once some lithium ions are deintercalated from the interlayer space between them, the displacement of two adjacent NiO2 layers will occur, resulting in a local region of O1-type stacking in most O3-layer stacking sequences. As additional lithium ions are deintercalated from the remaining interlayer regions, additional layer sliding will occur. When lithium ions are almost completely deintercalated, the remaining lattice can be transformed into an ordered hexagonal lattice with an ordered O1-type layer stacking order, where the repeating unit is a single NiO2 layer with AB oxygen stacking, such as Figure 5As shown in B. Figure 3 A typical XRD pattern of stoichiometric α-delithiated layered nickel oxide is shown in (below). The XRD pattern of stoichiometric α-delithiated layered nickel oxide is similar to that of the corresponding stoichiometric lithium nickelate precursor, with the expected peak shift corresponding to a slight expansion of the interlayer spacing due to the removal of most lithium ions and the resulting increase in electrostatic repulsion between NiO2 layers.
[0047] In the case of Li 1-a Ni 1+a In the case of non-stoichiometric lithium nickelates with a ratio of α to α (where 0.02 ≤ a ≤ 0.2), excess nickel may occupy lithium sites in the interlayer. The presence of excess nickel can be determined by ICP elemental analysis. The presence of nickel in lithium sites in the interlayer can also be detected by Rietveld refinement of the XRD pattern of the non-stoichiometric lithium nickelate. Figure 2 ] A comparison of the XRD patterns of non-stoichiometric lithium nickelate and stoichiometric lithium nickelate is shown in FIG.
[0048] The nickel ions present in the interlayers of the non-stoichiometric lithium nickelate precursor are typically present in the interlayers of the derived α-delithiated layered nickel oxide, and ultimately in the interlayers of the non-stoichiometric β-delithiated layered nickel oxide. Based on the ionic radius constraints of the octahedral lithium sites, the oxidation state of the nickel ions in the interlayers of the lithium nickelate is believed to be Ni (II). Without intending to be bound by theory, it is believed that due to the strong Ni-O bonding between adjacent NiO2 layers, the presence of nickel in the interlayers will stabilize the O3-type layer stacking order by locally inhibiting the sliding of the NiO2 layers relative to each other, even after almost all lithium ions have been deintercalated. Figure 5 An example of an O1-type lattice with an O3-type stacking fault is shown in C. The atomic fraction of Ni(II) ions present in the interlayers of the α-delithiated layered nickel oxide is in the range of about 0.03 to about 0.15 and the atomic fraction of residual lithium ions present in the interlayers is in the range of about 0.05 to 0.12.
[0049] α-Delithiated layered nickel oxide has a high electrochemical potential value and has been found to react with alkaline aqueous electrolyte solutions to generate oxygen via the oxygen evolution reaction (OER). In addition, due to OER, the discharge capacity of a battery containing such α-delithiated layered nickel oxide as an electrochemically active cathode material is generally reduced due to self-discharge. The evolution of oxygen during storage of a sealed battery can lead to an increase in internal pressure, resulting in electrolyte leakage or degassing (if the pressure is high enough). In addition, the consumption of water due to OER will reduce the amount of water available for electrochemical discharge reactions (which will consume water and generate protons and hydroxide ions) present inside the single cell and thus limit the accessible discharge capacity of the battery compared to the theoretical capacity. By treating the α-delithiated layered nickel oxide with an alkali metal hydroxide solution, the α-delithiated layered nickel oxide can be stabilized to significantly reduce the rate of OER, thereby increasing the capacity retention after storage. Treating the α-delithiated layered nickel oxide with an aqueous alkali metal hydroxide solution will introduce alkali metal cations and water molecules into the interlayers of the α-delithiated nickel oxide structure.
[0050] When an α-delithiated layered nickel oxide having a Ni (II) atomic fraction of about 0.03 to about 0.15 in the interlayer relative to the total nickel content (i.e., non-stoichiometric) is treated with an alkali metal hydroxide solution, the intercalation of alkali metals and water molecules into the interlayers results in the introduction of additional stacking faults into the non-stoichiometric α-delithiated layered nickel oxide structure. Materials containing alkali metals and water and other stacking faults are referred to as non-stoichiometric β-delithiated layered nickel oxide. Without intending to be bound by theory, it is believed that during the treatment with an alkali metal hydroxide solution, the O3-type stacking order of the α-delithiated layered nickel oxide is converted to an ordered O1-type stacking order with O3-type layer stacking faults in the bulk ordered O1-type lattice. In addition, during the treatment with alkali hydroxide solution, alkali metal ions along with water molecules may also be embedded in the ordered O1-type lattice to form another type of planar stacking fault including γ-nickel oxyhydroxide-like layers (γ-NiOOH-like), with a larger spacing between NiO2 layers (e.g., 11-12 angstroms) relative to the spacing between O3-type layers and O1-type layers (approximately 4.7 angstroms and 7.2 angstroms, respectively). The γ-NiOOH-like stacking fault has a P3-type layer stacking sequence, in which the repeating unit includes three NiO2 layers with oxygen in the AB BC CA stacking sequence. It is also believed that the nucleation of the γ-NiOOH-like layer may occur near the O3-type layer stacking fault, thereby providing structural stabilization by minimizing the strain energy at the interface between the O3-type layer stacking fault and the ordered O1-type lattice. Figure 4The characteristic XRD pattern of non-stoichiometric β-delithiated layered nickel oxide is shown in Figure 1. The presence of γ-NiOOH-like stacking faults is confirmed by the wide seventh peak at about 11° to 12° 2θ in the XRD pattern of non-stoichiometric β-delithiated layered nickel oxide. The typical lattice parameters of β-delithiated layered nickel oxide were determined by refinement of the XRD pattern: a = 2.839Å, c = 14.324Å (space group: R-3m).
[0051] In contrast, when a nominally stoichiometric α-delithiated layered nickel oxide having less than about 0.03 or less than about 0.02 atomic fraction of Ni(II) present in the interlayers relative to the total nickel content is treated with an alkali metal hydroxide solution, the α-delithiated layered nickel oxide is almost completely converted to a highly crystalline form of γ-nickel oxyhydroxide (γ-NiOOH), rather than the non-stoichiometric β-delithiated layered nickel oxide. Figure 4 As shown in (below), the powder XRD patterns of non-stoichiometric β-delithiated layered nickel oxide and γ-nickel oxyhydroxide can be easily distinguished. Figure 4 The XRD pattern shown below is obtained from γ-nickel oxyhydroxide prepared according to the synthesis method described by Arai et al. (Electrochimica Acta, 50 (2005) 1821-1828; Solid State Ionics, 80 (1995) 261-269). This XRD pattern is similar to the XRD pattern of γ-nickel oxyhydroxide material prepared by Arai (in Arai's Figure 1 e), confirming that the KOH-treated product of the delithiated lithium nickel oxide prepared from stoichiometric lithium nickel oxide is consistent with that of Arai et al. (Electrochimica Acta, 50 (2005) 1821-1828) are the same as the γ-nickel oxyhydroxide material prepared.
[0052] Surprisingly, it was found that when provided as an electrochemically active cathode material in an alkaline battery, the non-stoichiometric β-de-lithiation layered nickel oxide prepared by non-stoichiometric lithium nickel acid provides one or more advantages, including but not limited to reduced oxygen evolution rate, reduced self-discharge and increased capacity retention, relative to the α-de-lithiation layered nickel oxide active material prepared by stoichiometric or non-stoichiometric lithium nickel acid. For example, as shown in Table 3, when immersed in an alkaline KOH electrolyte solution, the oxygen evolution rate of the non-stoichiometric β-de-lithiation layered nickel oxide is about 50% or less of the oxygen evolution rate of the corresponding α-de-lithiation layered nickel oxide precursor. In contrast, non-stoichiometric lithium nickel acid and the α- and β-de-lithiation layered nickel oxide prepared therefrom are generally not suitable for use as cathode active materials in non-aqueous lithium ion rechargeable batteries. In particular, the presence of Ni(II) ions in the interlayer region of non-stoichiometric lithium nickel acid and the α- and β-de-lithiation layered nickel oxide prepared therefrom leads to a reduction in the distance between the NiO2 layers. This reduction in spacing hinders the rate and extent of lithium deintercalation and reintercalation, thereby limiting the overall discharge capacity and rate capability of non-aqueous lithium-ion secondary batteries.
[0053] The experimentally measured XRD patterns of non-stoichiometric β-delithiated layered nickel oxides can be simulated using the DIFFaX computer program. The amount of O3-type layer stacking faults and γ-NiOOH-like layer stacking faults present in an ordered O1-type layer stacking sequence can be statistically varied to estimate the relative amount of each stacking type that must be present to obtain the relative intensity, peak shape, and FWHM value of each peak in the experimentally measured XRD pattern. The DIFFaX program calculates the diffraction intensity for a given type of layer stacking sequence using an assumed stacking structure model. vs. 2θ. XRD patterns can be simulated by introducing increasing levels of both O3-type stacking faults and γ-nickel oxyhydroxide-like layers into an ordered O1-type oxygen stacking model. The simulated diffraction patterns can be refined using Rietveld analysis to identify the stacking fault structural model that best matches the experimental diffraction pattern. The transition probabilities of the O3-type and γ-nickel oxyhydroxide-like stacking faults used to generate the simulated diffraction patterns that best match the experimental diffraction patterns can be converted into stacking layer fractions.
[0054] Scanning transmission electron microscopy (STEM) imaging (e.g., Fig. 6A ) and convergent beam electron diffraction (CBED) of a single crystal (e.g., as shown in Figure 6B) to easily detect the presence of localized stacking faults in a bulk phase with a characteristic layer stacking order. Specifically, CBED measurements and STEM lattice imaging of single crystals in non-stoichiometric β-delithiated layered nickel oxide particles reveal the presence of low levels of secondary (and tertiary) layer stacking order as stacking faults in the majority of the stacking order in the layered structure of the bulk phase. Stacking faults are evident in STEM lattice images as abrupt changes in the periodicity of the lattice fringes and as changes in the corresponding row spacing of spots in the electron diffraction pattern. In the case of non-stoichiometric lithium nickel oxide, the presence of additional spots along the c-axis direction (relative to nominally stoichiometric lithium nickel oxide) is consistent with the presence of Ni ions in interlayer regions with different order along the c-axis. In the case of non-stoichiometric β-delithiated layered nickel oxide, there is evidence for the presence of an ordered O1-type stacking order with a row spacing of 7.2 Å and the presence of regions with a row spacing of 4.7 Å corresponding to O3-type layer stacking faults. In addition, O3-type stacking faults may be dispersed or aggregated together in the O1-type lattice.
[0055] Figure 7 B shows the simulated XRD pattern of non-stoichiometric β-delithiated layered nickel oxide generated by the DIFFaX program and can be compared with Figure 7A is compared with the corresponding experimentally measured XRD pattern in Figure 1. As described above, the simulated XRD pattern can be used to determine the stacking layer fraction. The non-stoichiometric β-delithiated layered nickel oxide has a layered structure characterized by a lattice comprising multiple NiO2 layers, wherein the NiO2 lattice contains an ordered O1-type layer stacking sequence, at least one O3-type layer stacking fault and at least one γ-nickel hydroxide-like layer stacking fault. The values of the layer fractions of ordered O1-type, O3-type and γ-nickel hydroxide-like stacking in the lattice structure of the non-stoichiometric β-delithiated layered nickel oxide that provides high discharge capacity in alkaline electrochemical cells can have a characteristic range. In particular, the NiO2 lattice may comprise about 60% to about 95% ordered O1-type layer stacking based on all layers, for example, about 65% to about 95%, about 60% to about 85%, about 70% to about 90%, about 85% to about 95%, about 75% to about 90%, about 80% to 90%, or about 84% to 88% ordered O1-type layer stacking, as determined using the DIFFaX program. Based on the total layers, the NiO2 lattice of the non-stoichiometric β-delithiated layered nickel oxide may contain about 2% to about 40% O3-type layer stacking faults, for example, about 2% to about 35%, about 2% to about 15%, about 2% to about 10%, about 4% to about 30%, about 4% to about 25%, about 6% to about 20%, about 6% to about 15%, about 7% to about 12%, about 7% to about 11%, about 15% to about 40%, about 25% to about 40%, or about 35% to about 40% O3-type layer stacking faults, as determined using the DIFFaX program. Based on the total layers, the NiO2 lattice of the non-stoichiometric β-delithiated layered nickel oxide may contain about 2% to about 5% γ-NiOOH-like layer stacking faults, for example, about 2%, about 3%, about 4%, or about 5% γ-NiOOH-like layer stacking faults, as determined using the DIFFaX program. The characteristic stacking fault structure of nonstoichiometric β-delithiated layered nickel oxide can be effectively defined by the amount of Ni(II) ions in the lithium layer and the stacking fault fraction range of O1-type layer stacking sequence, O3-type layer stacking fault and γ-nickel oxyhydroxide-like layer stacking fault statistically distributed in the lattice.
[0056] Thus, a method for determining and characterizing a non-stoichiometric β-delithiated layered nickel oxide capable of providing a high discharge capacity when included in a cathode of a primary alkaline battery includes analyzing x-ray diffraction and electron diffraction data using the DIFFaX program to simulate the experimental diffraction pattern using a structural model. A structural model can be developed to characterize one or more ordered layer stacking sequences and planar stacking faults present in the non-stoichiometric β-delithiated layered nickel oxide to determine whether the β-delithiated layered nickel oxide contains an ordered O1-type layer stacking sequence, at least one O3-type layer stacking fault, and at least one γ-nickel oxyhydroxide-like layer stacking fault, for example, about 60% to about 95% ordered O1-type layer stacking sequence, about 2% to about 40% O3-type layer stacking faults, and about 2% to about 5% γ-nickel oxyhydroxide-like layer stacking faults.
[0057] Non-stoichiometric β-delithiated layered nickel oxide can be prepared from non-stoichiometric α-delithiated layered nickel oxide, which in turn is prepared from non-stoichiometric lithium nickelate.
[0058] The non-stoichiometric lithium nickelate precursor may have the formula Li 1-a Ni 1+a O2, wherein 0.02 ≤ a < 0.2. The lithium nickelate may be doped with a metal M, wherein M is selected from an alkaline earth metal, a transition metal, a non-transition metal, and any combination thereof. The metal-doped lithium nickelate may have a formula Li 1-a Ni 1+a-z M z O2, wherein 0.02 ≤ a < 0.2 and 0 ≤ z < 0.2. Without intending to be bound by theory, it is believed that when a non-stoichiometric lithium nickelate having an amount of M greater than or equal to 20% of the amount of nickel is used as a starting material for a non-stoichiometric α-delithiated layered nickel oxide, the resulting non-stoichiometric α-delithiated layered nickel oxide will not form a non-stoichiometric β-delithiated layered nickel oxide when treated with an alkaline solution, but will form a γ-nickel oxyhydroxide. In addition, it is believed that when the lithium nickelate is a stoichiometric lithium nickelate (i.e., Li 1-a Ni 1+a O2, where 0 ≤ a<0.02), the α-delithiated layered nickel oxide prepared therefrom will form γ-nickel oxyhydroxide instead of non-stoichiometric β-delithiated layered nickel oxide when treated with an alkaline solution.
[0059] The non-stoichiometric α-delithiated layered nickel oxide comprises a chemical formula Li x H w Ni 1-aO2, wherein 0.02≤x≤0.2, 0≤w≤0.2 and 0.02≤a≤0.2. Methods for forming non-stoichiometric α-delithiated layered nickel oxide are well known in the art. Non-stoichiometric lithium nickelate can be chemically oxidized to form non-stoichiometric α-delithiated layered nickel oxide. Suitable chemical oxidants for forming α-delithiated layered nickel oxide from lithium nickelate include, but are not limited to, sodium hypochlorite, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium permanganate, potassium permanganate, sodium dichromate, potassium dichromate, ozone gas, chlorine, bromine, sulfuric acid, hydrochloric acid and nitric acid. The α-delithiated layered nickel oxide may further comprise a metal M selected from alkaline earth metals, transition metals, non-transition metals and any combination thereof. Non-stoichiometric α-delithiated layered nickel oxide comprising a metal dopant M can be prepared from a metal-doped non-stoichiometric lithium nickelate precursor. In addition, the interlayer region of the α-delithiated layered nickel oxide contains almost the same atomic fraction of Ni(II) ions as that in the interlayer region of the lithium nickelate precursor.
[0060] In the case of lithium nickelate treated with strong mineral acids, the Ni(III) ions undergo an acid-promoted disproportionation reaction, resulting in the formation of equal parts of soluble Ni(II) and insoluble Ni(IV). The disproportionation reaction can be summarized in Equation 1 as follows:
[0061]
[0062] The Ni(II) species is soluble and dissolves in aqueous acid solutions, whereas the Ni(IV) species is insoluble and remains to maintain the layered lattice structure.
[0063] The non-stoichiometric β-delithiated layered nickel oxide comprises a chemical formula Li x A y Ni 1+a-z M zO2•nH2O, wherein x is from about 0.02 to about 0.20; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; n is from about 0 to about 1; A includes alkali metals including potassium, rubidium, cesium, and any combination thereof; M includes alkaline earth metals, transition metals, non-transition metals, and any combination thereof. The non-stoichiometric β-delithiated layered nickel oxide is prepared by treating the non-stoichiometric α-delithiated layered nickel oxide with an alkaline solution containing an alkali metal salt. The alkaline solution is not particularly limited and may be selected from a potassium salt solution, a rubidium salt solution, a cesium salt solution, or any combination thereof. The alkaline solution may be prepared from an alkali metal salt and water, such as an alkali metal hydroxide solution. The concentration of the alkali metal salt in the alkaline solution must be sufficient to achieve complete conversion of the α-delithiated layered nickel oxide to the non-stoichiometric β-delithiated layered nickel oxide. In some embodiments, the concentration of the alkali metal salt in the solution may be in the range of about 0.5M to about 10M. In some embodiments, the alkaline solution comprises at least one of potassium hydroxide, cesium hydroxide, and rubidium hydroxide provided at a concentration of about 0.5M to about 10M. The non-stoichiometric α-delithiated layered nickel oxide may be provided as a free-flowing powder. The non-stoichiometric α-delithiated layered nickel oxide powder and the alkaline solution may be combined in a weight ratio of about 5:1 to about 1:2, or about 4:1 to about 1:2, or about 3:1 to about 1:1, for example, about 3:1, about 2:1, or about 1:1.
[0064] The non-stoichiometric α-delithiated layered nickel oxide can be treated with an alkaline solution for a period of time sufficient to ensure that the non-stoichiometric α-delithiated layered nickel oxide is completely converted to the non-stoichiometric β-delithiated layered nickel oxide. The non-stoichiometric α-delithiated layered nickel oxide and the alkaline solution can be first stirred at ambient temperature for 5 to 15 minutes to ensure adequate mixing and wetting. After the non-stoichiometric α-delithiated layered nickel oxide and the alkaline solution are mixed, the mixture is maintained at ambient temperature for 2 to 24 hours. Optionally, the mixture can be stirred during this 2 to 24 hour period. The complete conversion to the non-stoichiometric β-delithiated layered nickel oxide can be determined by analyzing the powder X-ray diffraction pattern. For example, when non-stoichiometric α-delithiated layered nickel oxide is converted to non-stoichiometric β-delithiated layered nickel oxide, the peak intensity at about 18° to 20° 2θ in the X-ray diffraction pattern of the non-stoichiometric α-delithiated layered nickel oxide decreases and very broad peaks are produced at about 14.9° to about 16.0° 2θ and about 21.3° to about 22.7° 2θ in the X-ray diffraction pattern of the non-stoichiometric β-delithiated layered nickel oxide. Thus, upon complete conversion to non-stoichiometric β-delithiated nickel oxide, the powder X-ray diffraction pattern will have broad peaks at about 10.8° to about 12.0° 2θ, about 14.9° to about 16.0° 2θ, and about 31.3° to about 22.7° 2θ, which peaks have greater intensity than in the powder X-ray diffraction pattern of the non-stoichiometric α-delithiated layered nickel oxide precursor, and there is no peak with significant intensity in the range of about 18° to 20° 2θ. The resulting non-stoichiometric β-delithiated layered nickel oxide can be repeatedly washed with deionized water until the pH of the filtrate from the washing is about 10. The solid powder can be collected and dried in air at about 70° C. for a period of about 12 to 20 hours.
[0065] In alkaline cells, the electrochemically active cathode material is reduced during discharge and water from the alkaline electrolyte within the cell is simultaneously consumed. This results in the formation of hydroxide ions and the insertion of protons into the structure of the electrochemically active cathode material. For example, a conventional alkaline cell may contain electrolytic manganese dioxide (EMD) as the electrochemically active cathode material. In such a conventional alkaline cell, one mole of water may be consumed for each mole of manganese present in the 4+ oxidation state, which manganese may be reduced to manganese in the 3+ oxidation state by a 1-electron reduction process. For example, a non-conventional alkaline cell may contain a non-stoichiometric β-delithiated layered nickel oxide as the electrochemically active cathode material. The non-stoichiometric β-delithiated layered nickel oxide may, for example, have the chemical formula Li 0.07 K 0.13 Ni 1.11O2 •0.63H2O. In such non-conventional alkaline cells, up to two moles of water may be consumed for each mole of nickel present in the 4+ oxidation state, which may be reduced to nickel in the 2+ oxidation state by a 2-electron reduction process. Additionally, one mole of water may be consumed for each mole of nickel present in the 3+ oxidation state, which may be reduced to nickel in the 2+ oxidation state by a single electron reduction process. Thus, electrochemical discharge of a cell containing β-delithiated layered nickel oxide may require more than one mole of water per mole of nickel to achieve complete discharge. Additionally, excess water may be required to minimize polarization of the anode during discharge and to compensate for water consumed by self-discharge during storage of the cell. The amount of excess water that may be required depends on the specific chemical composition of the non-stoichiometric β-delithiated layered nickel oxide and the relative amounts of nickel in the 4+ and 3+ oxidation states. Water may be introduced into the cell via an aqueous alkaline electrolyte solution and as a moisture content of the non-stoichiometric β-delithiated layered nickel oxide. The alkaline electrolyte may be distributed throughout the cell. The total amount of water present in the cell may be increased by various methods. For example, the amount of water can be increased by increasing the total amount of alkaline electrolyte added to the cell. In addition, the amount of water in the cell can be increased by reducing the potassium hydroxide concentration of the electrolyte solution. In contrast, in conventional alkaline cells, it is desirable to add a minimum total volume of electrolyte to the cell to maximize the internal volume available for electrochemically active electrode materials.
[0066] The cathode 12 may include a non-stoichiometric β-delithiated layered nickel oxide as an electrochemically active cathode material. As used herein, "non-stoichiometric β-delithiated layered nickel oxide" refers to a non-stoichiometric delithiated layered nickel oxide separated in a "β" form. Thus, for example, when a non-stoichiometric β-delithiated layered nickel oxide is provided as an electrochemically active cathode material, the non-stoichiometric β-delithiated layered nickel oxide contains less than 5 wt%, less than 3 wt%, less than 1 wt%, or less than 0.5 wt% of residual non-stoichiometric α-delithiated layered nickel oxide based on the total weight of the delithiated layered nickel oxide electrochemically active cathode material. Similarly, as described herein, a single cell including a non-stoichiometric β-delithiated layered nickel oxide has a non-stoichiometric β-delithiated layered nickel oxide from the outset.
[0067] Cathode 12 may also include at least one or more additional electrochemically active cathode materials. The additional electrochemically active cathode materials may include manganese oxide, manganese dioxide, electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high performance electrolytic manganese dioxide (HP EMD), λ-manganese dioxide, γ-manganese dioxide, and any combination thereof. Other electrochemically active cathode materials include, but are not limited to, silver oxide; nickel oxide, nickel oxyhydroxide; copper oxide; silver copper oxide; silver nickel oxide; bismuth oxide; oxygen; and any combination thereof. Nickel oxyhydroxide may include β-nickel oxyhydroxide, γ-nickel oxyhydroxide, β-nickel oxyhydroxide and / or a co-product of γ-nickel oxyhydroxide, and nickel oxyhydroxide coated with cobalt oxyhydroxide. Nickel oxyhydroxide coated with cobalt oxyhydroxide may include β-nickel oxyhydroxide coated with cobalt oxyhydroxide, γ-nickel oxyhydroxide coated with cobalt oxyhydroxide, and / or a co-product of β-nickel oxyhydroxide coated with cobalt oxyhydroxide and γ-nickel oxyhydroxide.
[0068] In embodiments, the electrochemically active material of cathode 12 comprises at least 10 wt % of a non-stoichiometric β-delithiated layered nickel oxide having the general formula Li x A y Ni 1+a-z M zO2•nH2O, wherein x is from about 0.03 to about 0.12; y is from about 0.03 to about 0.20; a is from about 0.02 to about 0.2; z is from about 0 to about 0.2; n is from about 0 to about 1; A comprises an alkali metal; M comprises an alkaline earth metal, a transition metal, a non-transition metal, and any combination thereof, based on the total weight of the electrochemically active cathode material; the remaining electrochemically active cathode material comprises one or more of manganese oxide, manganese dioxide, electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high performance electrolytic manganese dioxide (HP EMD), λ-manganese dioxide, or γ-manganese dioxide. In embodiments, the electrochemically active material of cathode 12 comprises at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, at least 45 wt%, at least 50 wt%, at least 55 wt%, at least 60 wt%, at least 70 wt%, or at least 75 wt% of non-stoichiometric β-delithiated layered nickel oxide, based on the total weight of the electrochemically active cathode material, for example, in a range of about 10 wt% to about 90 wt%, about 10 wt% to about 80 wt%, about 20 wt% to about 70 wt%, about 30 wt% to about 60 wt%, about 40 wt% to about 60 wt%, or about 50 wt%, based on the total weight of the electrochemically active cathode material. In an embodiment, the electrochemically active material of cathode 12 comprises about 40 wt % to about 60 wt % of non-stoichiometric β-delithiated nickel oxide based on the total weight of the electrochemically active cathode material and about 60 wt % to about 40 wt % of one or more of the following based on the total weight of the electrochemically active cathode material: manganese oxide, manganese dioxide, electrolytic manganese dioxide (EMD), chemical manganese dioxide (CMD), high performance electrolytic manganese dioxide (HP EMD), λ-manganese dioxide or γ-manganese dioxide. The combination of between about 10 wt % to about 60 wt %, such as 20 wt % or 50 wt %, of non-stoichiometric β-delithiated layered nickel oxide with the remainder being an electrochemically active cathode material comprising electrolytic manganese dioxide (EMD) has been found to provide unexpectedly advantageous battery performance in both high discharge rate applications and low rate discharge applications.
[0069] The cathode 12 may include conductive additives such as carbon and optional binders. The cathode 12 may also include other additives. Carbon can increase the conductivity of the cathode 12 by promoting the transport of electrons in the solid structure of the cathode 12. Carbon can be graphite, such as natural graphite, synthetic graphite, oxidation-resistant graphite, graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon fibers, carbon nanofibers, carbon nanobelts, carbon flake nanoparticles and mixtures thereof. The amount of carbon in the preferred cathode is relatively low, for example, less than about 12%, less than about 10%, less than about 9%, less than about 8%, less than about 6%, less than about 5%, less than about 3.75%, or even less than about 3.5%, such as about 3.0% to about 5% by weight or about 2.0% to about 3.5% by weight. Lower carbon content allows the inclusion of a higher load of electrochemically active cathode material in the cathode 12 without increasing the volume of the cathode 12 or reducing the void volume in the battery 10 (the void volume must be maintained at a certain level or above to prevent the internal pressure from rising too high as the gas is generated in the single cell). Suitable graphites for use in the battery (e.g., in the cathode) may be, for example, Timrex MX-15, SFG-15, MX-25, all of which are available from Imerys Graphite and Carbon (Bodio, Switzerland). In the case of highly reactive cathode active materials such as non-stoichiometric β-delithiated layered nickel oxide, oxidation resistant graphites such as SFG-15, SFG-10, and SFG-6 may be used.
[0070] Cathode 12 may include an optional binder. As used herein, "binder" refers to a polymer material that provides cathode cohesion and does not include graphite. Examples of optional binders that can be used in cathode 12 include polyethylene, polyacrylic acid or fluorocarbon resins, such as PVDF or PTFE. The optional binder used in cathode 12 can be, for example, COATHYLENE HA-1681 available from EI du Pontde Nemours and Company (Wilmington, DE, USA). Examples of other cathode additives are described in, for example, U.S. Patent Nos. 5,698,315, 5,919,598, 5,997,775 and 7,351,499. In some embodiments, cathode 12 is substantially free of binder. As used herein, "substantially free of binder" refers to a cathode that contains less than about 5% by weight, less than about 3% by weight or less than about 1% by weight of binder.
[0071] The content of electrochemically active cathode material in cathode 12 can be referred to as cathode loading. The loading of cathode 12 can vary depending on the electrochemically active cathode material used in battery 10 and the size of battery 10. For example, a AA battery having β-delithiated layered nickel oxide as the electrochemically active cathode material can have a cathode loading of at least about 6 grams of β-delithiated layered nickel oxide. The cathode loading can be, for example, at least about 7 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading can be, for example, between about 7.2 grams and about 11.5 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading can be about 8 grams to about 10 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading can be about 8.5 grams to about 9.5 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading can be about 9.5 grams to about 11.5 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading may be about 10.4 grams to about 11.5 grams of non-stoichiometric β-delithiated layered nickel oxide. For AAA batteries, the cathode loading may be at least about 3 grams of non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode material. The cathode loading may be about 3 grams to about 5 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading may be about 3.5 grams to about 4.5 grams of non-stoichiometric β-delithiated layered nickel oxide. The cathode loading may be about 3.9 grams to about 4.3 grams of non-stoichiometric β-delithiated layered nickel oxide. For AAAA batteries, the cathode loading may be about 1.5 grams to about 2.5 grams of non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode material. For C batteries, the cathode loading may be about 27.0 grams to about 40.0 grams, for example, about 35.5 grams of non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode material. For a D cell, the cathode loading may be from about 60.0 grams to about 84.0 grams, such as about 72.0 grams, of the non-stoichiometric beta-delithiated layered nickel oxide electrochemically active cathode material.
[0072] Cathode components such as one or more active cathode materials, carbon particles, binders, and any other additives may be combined with a liquid such as an aqueous potassium hydroxide electrolyte, blended, and pressed into pellets for use in the assembly of the battery 10. For optimal cathode pellet processing, it is generally preferred that the cathode pellets have a moisture content in the range of about 2 wt % to about 5 wt %, or about 2.8 wt % to about 4.6 wt %. The pellets are placed in the housing 18 during the assembly of the battery 10 and are typically re-compacted to form a uniform cathode assembly in the housing 18. The cathode pellets may have a cylindrical shape including a central hole. The size of the pellets may vary depending on the size of the battery in which the pellets will be used, such as AA size, AAA size, AAAA size, C size, and D size. The central hole may define the inner diameter (ID) of the pellets. The inner diameter of the pellets for AA batteries may, for example, be about 9.1 mm to about 9.9 mm. The inner diameter of the pellets for AA batteries may, for example, be about 9.3 mm to about 9.7 mm. The inner diameter of the pellet for AAA battery can be, for example, about 6.6 mm to about 7.2 mm. The inner diameter of the pellet for AAA battery can be, for example, about 6.7 mm to about 7.1 mm. The inner diameter of the pellet for AAAA battery can be, for example, about 5 mm to about 5.5 mm. The inner diameter of the pellet for C battery can be, for example, about 16 mm to about 19 mm. The inner diameter of the pellet for D battery can be, for example, about 21 mm to about 25 mm.
[0073] The cathode 12 will have a certain porosity, which can be calculated when the cathode is manufactured. The porosity of the cathode 12 can be about 20% to about 40%, between about 22% to about 35%, for example, about 26%. The porosity of the cathode 12 can be calculated at the time of manufacture, for example after the cathode pellet is processed, because the porosity of the cathode 12 in the battery 10 may change over time, especially due to cathode swelling associated with electrolyte wetting of the cathode and discharge of the battery 10. The porosity of the cathode 12 can be calculated as follows. The true density of each solid cathode component can be taken from a reference book, such as Lange's Handbook of Chemistry (16th edition, 2005). The solid weight of each cathode component is limited by the design of the battery. The solid volume of the cathode can be determined by dividing the solid weight of each cathode component by the true density of each cathode component. The volume occupied by the cathode 12 in the battery 10 is also limited by the design of the battery. The volume occupied by the cathode 12 can be calculated by a computer-aided design (CAD) program. The porosity can be determined by the following formula:
[0074]
[0075] For example, the cathode 12 of a AA battery may include about 9.0 grams of non-stoichiometric β-delithiated layered nickel oxide and about 0.90 grams of graphite (BNC-30) as solids within the cathode 12. The true densities of the non-stoichiometric β-delithiated layered nickel oxide and graphite may be about 4.9 g / cm 3 and about 2.15g / cm 3 The weight of the solid divided by the corresponding true density gives a volume occupied by the nonstoichiometric β-delithiated layered nickel oxide of approximately 1.8 cm 3 The volume occupied by graphite is about 0.42 cm 3 The total solid volume is about 2.2 cm 3 The cell designer may choose the volume occupied by cathode 12 to be approximately 3.06 cm 3 . Calculate the cathode porosity [1-(2.2cm 3 ÷3.06cm 3 )], the cathode porosity is found to be about 0.28, or 28%.
[0076] Anode 14 may be formed of at least one electrochemically active anode material, a gelling agent, and a small amount of additives such as organic and / or inorganic gassing inhibitors. The electrochemically active anode material may include zinc; zinc oxide; zinc hydroxide; metal hydrides such as AB5(H), AB2(H), and A2B7(H); alloys thereof; and any combination thereof.
[0077] The content of electrochemically active anode material in anode 14 may be referred to as anode loading. The loading of anode 14 may vary with the electrochemically active anode material used in the battery and the size of the battery. For example, an AA battery with a zinc electrochemically active anode material may have an anode loading of at least about 3.3 grams of zinc. The anode loading may, for example, be at least about 3.5 grams, about 3.7 grams, about 3.9 grams, about 4.1 grams, about 4.3 grams, or about 4.5 grams of zinc. The anode loading may be about 4.0 grams to about 5.5 grams of zinc. The anode loading may be about 4.2 grams to about 5.3 grams of zinc. For example, an AAA battery with a zinc electrochemically active anode material may have an anode loading of at least about 1.8 grams of zinc. For example, the anode loading may be about 1.8 grams to about 2.5 grams of zinc. The anode loading may, for example, be about 1.9 grams to about 2.4 grams of zinc. For example, an AAAA battery with a zinc electrochemically active anode material may have an anode loading of at least about 0.6 grams of zinc. For example, the anode loading may be from about 0.7 grams to about 1.3 grams of zinc. For example, a C cell having a zinc electrochemically active anode material may have an anode loading of at least about 9.3 grams of zinc. For example, the anode loading may be from about 10.0 grams to about 19.0 grams of zinc. For example, a D cell having a zinc electrochemically active anode material may have an anode loading of at least about 30.0 grams of zinc. For example, the anode loading may be from about 30.0 grams to about 45.0 grams of zinc. The anode loading may, for example, be from about 33.0 grams to about 39.5 grams of zinc.
[0078] Examples of gelling agents that can be used in the anode 14 include polyacrylic acid; polyacrylic acid cross-linked with a polyalkenyl ether of divinyl glycol; grafted starch materials; salts of polyacrylic acid; carboxymethyl cellulose; salts of carboxymethyl cellulose (e.g., sodium carboxymethyl cellulose); or combinations thereof. The anode 14 may include a gassing inhibitor, which may include an inorganic material such as bismuth, tin, or indium. Alternatively, the gassing inhibitor may include an organic compound such as a phosphate, an ionic surfactant, or a nonionic surfactant. The electrolyte may be dispersed throughout the cathode 12, the anode 14, and the separator 16. The electrolyte includes an ion-conducting component in an aqueous solution. The ion-conducting component may be an alkali metal hydroxide. The hydroxide may be, for example, potassium hydroxide, cesium hydroxide, and any combination thereof. The concentration of the ion-conducting component may be selected according to the design of the battery and its desired performance. An aqueous alkaline electrolyte may include a hydroxide as an ion-conducting component in a solution with water. The concentration of the alkali metal hydroxide in the electrolyte may be from about 0.20 to about 0.40, i.e., from about 20% to about 40%, based on the weight of the total electrolyte in the battery 10. For example, the hydroxide concentration of the electrolyte may be about 0.25 to about 0.32, i.e., about 25% to about 32%, based on the weight of the total electrolyte in the battery 10. The aqueous alkaline electrolyte may also include zinc oxide (ZnO). ZnO may be used to inhibit zinc corrosion in the anode. The concentration of ZnO included in the electrolyte may be less than about 5% by weight of the total electrolyte in the battery 10. For example, the ZnO concentration may be about 1% to about 3% by weight of the total electrolyte in the battery 10.
[0079] The total weight of the aqueous alkaline electrolyte in an AA alkaline battery may be, for example, about 3.0 grams to about 4.4 grams. The total weight of the alkaline electrolyte in an AA battery may be, for example, about 3.3 grams to about 3.8 grams. The total weight of the alkaline electrolyte in an AA battery may be, for example, about 3.4 grams to about 3.65 grams. The total weight of the aqueous alkaline electrolyte in an AAA alkaline battery may be, for example, about 1.0 grams to about 2.0 grams. The total weight of the electrolyte in an AAA battery may be, for example, about 1.2 grams to about 1.8 grams. The total weight of the electrolyte in an AAA battery may be, for example, about 1.4 grams to about 1.8 grams. The total weight of the electrolyte in an AAAA battery may be, for example, about 0.68 grams to about 1 gram, for example, about 0.85 grams to about 0.95 grams. The total weight of the electrolyte in a C battery may be, for example, about 11 grams to about 14 grams, for example, about 12.6 grams to about 13.6 grams. The total weight of the electrolyte in a D battery may be, for example, about 22 grams to about 30 grams, for example, about 24 grams to about 29 grams.
[0080] The separator 16 comprises a material that can be wetted by the electrolyte or is wetted by the electrolyte. When the contact angle between the liquid and the surface of the material is less than 90° or when the liquid tends to spread spontaneously on the surface of the material - these two conditions usually coexist, the material is said to be wetted by the liquid. The separator 16 may include a single layer or multiple layers of woven or non-woven paper or fabric. The separator 16 may include, for example, a layer of cellophane combined with a layer of non-woven material. The separator 16 may also include additional layers of non-woven material. The separator 16 may also be formed in situ in the battery 10. For example, U.S. Patent 6,514,637 discloses such a separator material and its potentially suitable application method. The separator material may be very thin. For example, the separator 16 may have a dry material thickness of less than 250 microns (µm). The separator 16 may have a dry material thickness of about 50 microns to about 175 microns. The separator 16 may have a dry material thickness of about 70 microns to about 160 microns. The separator 16 may have a dry material thickness of about 40 g / m 2 The separator 16 may have a basis weight of about 15 g / m 2 About 40g / m 2 The separator 16 may have a basis weight of about 20 g / m 2 About 30g / m 2 The membrane 16 may have an air permeability value as defined in International Organization for Standardization (ISO) Standard 2965. The air permeability value of the membrane 16 may be about 2000 cm 3 / cm 2 ·min @1kPa to about 5000cm 3 / cm 2 ·min @ 1kPa. The air permeability value of the separator 16 may be about 3000cm 3 / cm 2 •min @ 1kPa to about 4000cm 3 / cm 2 •min @ 1kPa. The air permeability value of the separator 16 may be about 3500cm 3 / cm 2 •min @ 1kPa to about 3800cm 3 / cm 2 •min @ 1kPa.
[0081] The collector 20 can be made into any suitable shape for a specific battery design by any known method in the art. The collector 20 can have, for example, a nail-like shape. The collector 20 can have a cylindrical body and a head at one end of the cylinder. The collector 20 can be made of a metal, such as zinc, copper, brass, silver, or any other suitable material. The collector 20 can optionally be plated with tin, zinc, bismuth, indium, or other suitable materials that present a low electrical contact resistance between the collector 20 and, for example, the anode 14. When the collector 20 is in contact with the anode 14, the plating material can also exhibit the ability to inhibit gas formation.
[0082] The seal 22 can be prepared by injection molding a polymer such as polyamide, polypropylene, polyether urethane, etc.; a polymer composite material; and any combination thereof into a shape having a predetermined size. The seal 22 can be made of, for example, nylon 6,6, nylon 6,10, nylon 6,12, nylon 11, polypropylene, polyether urethane, copolymers, composite materials, and any combination thereof. Exemplary injection molding methods include both cold runner methods and hot runner methods. The seal 22 may contain other known functional materials such as plasticizers, crystal nucleating agents, antioxidants, mold release agents, lubricants, and antistatic agents. The seal 22 may also be coated with a sealant. The seal 22 may be humidified before use in the battery 10. For example, the seal 22 may have a moisture content of about 1.0 wt % to about 9.0 wt %, depending on the seal material. The collector 20 may be inserted into the seal 22 and pass through the seal 22.
[0083] The end cap 24 may be formed into any shape sufficient to enclose the battery. The end cap 24 may have, for example, a cylindrical or prismatic shape. The end cap 24 may be formed by pressing a material into a desired shape having suitable dimensions. The end cap 24 may be made of any suitable material that will conduct electrons during the discharge process of the battery 10. The end cap 24 may be made of, for example, nickel-plated steel or tin-plated steel. The end cap 24 may be electrically connected to the collector 20. The end cap 24 may be electrically connected to the collector 20, for example, by welding to the collector 20. The end cap 24 may also include one or more holes, such as holes, for discharging any gas pressure due to electrolyte leakage or for discharging battery exhaust gas accumulated due to excessive internal pressure. The collector 20, the seal 22, and the end cap 24 may be collectively referred to as an end cap assembly.
[0084] Battery 10 including cathode 12 having non-stoichiometric β-delithiated layered nickel oxide can have an open circuit voltage (OCV), which is measured in volts. Battery 10 can have an OCV of about 1.7 V to about 1.8 V. Battery 10 can have an OCV of, for example, about 1.76 V.
[0085] Batteries containing the non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode materials of the present invention can have improved discharge performance for low, medium and high discharge rates compared to, for example, conventional alkaline batteries. Batteries containing the non-stoichiometric β-delithiated layered nickel oxide electrochemically active cathode materials of the present invention can have higher open circuit voltages than, for example, conventional alkaline batteries.
[0086] Experimental testing
[0087] Elemental analysis by ICP-AES of β-delithiated layered nickel oxide electrochemically active materials
[0088] Elemental analysis was performed on a sample of a non-stoichiometric β-delithiated layered nickel oxide electrochemically active material by ICP-AES to determine the elemental composition of the sample material. ICP-AES analysis was performed using a HORIBA Scientific Ultima 2 ICP spectrometer. ICP-AES analysis was performed by placing the sample solution in the spectrometer. The preparation of the sample solution depends on the element or elements to be analyzed.
[0089] For elemental analysis, the first solution is formed by adding 0.15g sample material to 2ml deionized water (DI) and 5ml concentrated hydrochloric acid (HCl). The sample is gently rotated to mix the contents and then placed in a CEM Discover SP-D automatic microwave digestion system. While stirring the sample, the microwave system is allowed to climb to 180°C in 3 minutes and then maintained at 180°C for 4 minutes. The maximum power setting of the system is 300W, and the pressure setting point is 225PSI. The second solution is formed by adding the first solution to a 100ml volumetric flask and diluting to the mark with deionized water. The second solution is used for elemental analysis of lithium (Li), potassium (K) and rubidium (Rb) using an ICP-AES spectrometer. A third solution was formed by transferring 1 mL of the second solution to a 50 mL centrifuge tube, adding about 2.5 mL of concentrated HCl to the centrifuge tube, adding distilled water to the centrifuge tube so that the total weight of the sixth solution was 50 grams, and mixing the components of the centrifuge tube; the third solution was used for elemental analysis of nickel (Ni) using an ICP-AES spectrometer.
[0090] ICP-AES analysis of non-stoichiometric β-delithiated layered nickel oxide electrochemically active materials is performed at various wavelengths specific to potassium (K), lithium (Li), nickel (Ni), and rubidium (Rb). For example, the wavelength (λ) for analyzing potassium (K) in non-stoichiometric β-delithiated layered nickel oxide can be set at about 766 nm. For example, the wavelength (λ) for analyzing lithium (Li) in non-stoichiometric β-delithiated layered nickel oxide can be set at about 610 nm. For example, the wavelength (λ) for analyzing nickel (Ni) in non-stoichiometric β-delithiated layered nickel oxide can be set at about 231 nm. For example, the wavelength (λ) for analyzing rubidium (Rb) in non-stoichiometric β-delithiated layered nickel oxide can be set at about 780 nm.
[0091] Table 1 below includes elemental analysis of various samples of non-stoichiometric β-delithiated layered nickel oxide electrochemically active materials and γ-nickel oxyhydroxide materials prepared by the synthesis method described in Arai et al. (Electrochimica Acta, 50 (2005) 1821-1828; Solid State Ionics, 80 (1995) 261-269) by ICP-AES results. The weight percentages of lithium (Li), nickel (Ni) and potassium (K) within the sample materials are reported. Elemental analysis of ICP-AES data was used to determine the chemical composition of non-stoichiometric β-delithiated layered nickel oxide samples and γ-nickel oxyhydroxide materials prepared by the synthesis method described in Arai et al. (Electrochimica Acta, 50 (2005) 1821-1828; Solid State Ionics, 80 (1995) 261-269). Elemental analysis by ICP-AES was also used to confirm the non-stoichiometry and the presence of excess nickel within the non-stoichiometric β-delithiated layered nickel oxide composition.
[0092] Determination of water content by thermogravimetric analysis (TGA) of β-delithiated layered nickel oxide electrochemically active materials
[0093] Water content determination was performed on samples of non-stoichiometric β-delithiated layered nickel oxide electrochemically active materials by TGA to determine the absorbed / adsorbed water content, crystal water content, and total water content within the sample material. TGA analysis was performed using a TA Instruments Q5000 analyzer.
[0094] TGA analysis is performed by placing about 34 mg of sample on a TGA sample holder. The sample material is heated to a temperature of about 800° C. at a rate of 5° C. / min. The heating of the sample is performed in the presence of nitrogen, which flows at a rate of, for example, about 25 mL / min. The change in sample weight over time and temperature is measured.
[0095] Table 1 also includes the water content of the non-stoichiometric β-delithiated layered nickel oxide samples measured by TGA. The water content measured by TGA is used to determine the structural lattice water present in the chemical composition of the non-stoichiometric β-delithiated layered nickel oxide electrochemically active material. The water content measured by TGA can be used to determine the water physically adsorbed on the surface of the non-stoichiometric β-delithiated layered nickel oxide particles.
[0096] Table 1: ICP-AES and TGA data of non-stoichiometric β-delithiated nickel oxide electrochemically active materials and γ-nickel oxyhydroxide
[0097]
[0098] Powder X-ray diffraction analysis
[0099] Crystalline powder samples were subjected to powder X-ray diffraction (XRD) analysis using a Bruker D-8 Advance X-ray diffractometer to determine the characteristic XRD diffraction patterns of the crystallized powder samples. Various samples of non-stoichiometric β-delithiation layered nickel oxide and several comparative samples were obtained using Cu Kα radiation and a Sol-X detector (Baltic Scientific Instruments, Riga, Latvia). About one gram to about two grams of sample material was placed in a Bruker sample holder. The sample holder containing the sample material was then placed in a rotating sample stage of an X-ray diffractometer and then irradiated with the CuKα X-ray source of the diffractometer. The Diffrac-plus software provided by Bruker was then used to collect XRD patterns from 10°2θ to 80°2θ at 2 seconds / step with a step length of 0.02°. The EVA and Topas data analysis software packages (BrukerAXS Inc.) were used for analysis and refinement of the diffraction patterns. The XRD patterns of the samples were compared with the reference XRD patterns in the PDF-4+ database (International Center for Diffraction Data, ICDD).
[0100] Structural model of β-delithiated layered nickel oxide
[0101] In order to elucidate the nature of the high-level dislocation structure of nonstoichiometric β-delithiated layered nickel oxide, DIFFaX computer simulation was used to reproduce the experimentally measured X-ray diffraction pattern. The DIFFaX program assumes that a crystalline solid can be formally constructed by stacking planar layers of atoms (ions) and calculates the diffraction intensity of a given stacking order layer by layer. vs.The X-ray diffraction pattern is calculated by integrating the 2θ diffraction angle. In the case of non-stoichiometric β-delithiated layered nickel oxide, the NiO2 layer is constructed using the same atomic positions as those used to simulate the ideal layered R-3m structure. The NiO2 layer is then stacked along the c-axis direction and a translation (i.e., stacking) vector is applied to introduce the presence of a specific type of stacking fault, such as O3, O1, and P3. The simulation introduces a random distribution of stacking faults. In order to introduce specific stacking faults, different stacking vectors are used. The possibility of applying each stacking vector can be changed until a satisfactory match between the calculated X-ray diffraction pattern and the experimental X-ray diffraction pattern is achieved. The fit of the simulation is evaluated by Rietveld analysis of the simulated spectrum relative to the experimental spectrum.
[0102] A detailed structural model describing the characteristic stacking fault structure of non-stoichiometric β-delithiated layered nickel oxide is proposed by analyzing X-ray diffraction patterns, lattice imaging by scanning transmission electron microscopy (STEM), and electron diffraction (CBED) patterns. The characteristic diffraction peak intensities, peak positions, and peak widths of the experimental X-ray diffraction patterns are simulated by introducing increased levels of O3-type layer stacking faults into the ordered O1-type lattice using the DIFFaX software. The presence of a small fraction of O3-type layer stacking faults may also be related to certain structural (i.e., growth) defects and nickel (II) ions located at lithium ion sites in the interlayers. Without intending to be bound by theory, it is believed that in the process of forming the non-stoichiometric β-delithiated layered nickel oxide, Ni 2+ The migration of ions into interlayer sites previously occupied by lithium ions in non-stoichiometric α-delithiated layered nickel oxide leads to the ordering of metal-containing layers in the O1-type stacking sequence, so that the Ni-containing layers are aggregated along the c-axis. This can lead to an ordered O1-type lattice in which oxygen atoms are cubically closely packed and include a stacking order of metal-containing layers, wherein two nickel-containing layers separate each lithium-containing layer so that the order along the c-axis is, for example, -O-Li-O-Ni-O-Ni-O-Li-O-, rather than -O-Li-O-Ni-Li-O-Ni-O-, which is the order of metal-containing layers in the case of α-delithiated layered nickel oxide. The formation of adjacent Ni-containing layers is both systematic and periodic. In addition, it is believed that another type of planar stacking fault may be caused by the insertion of alkali metal ions and water molecules during the KOH treatment, which has a layer structure closely related to the layer structure of γ-hydroxy nickel oxide. γ-Ni(II) oxyhydroxide is reported to have an oxygen stacking order of AB BC CA (i.e., P3-type stacking). The introduction of this P3-type stacking fault in the ordered O1 lattice is confirmed by the appearance of broad low-intensity diffraction peaks at about 10.8° to about 12.0° 2θ in the simulated X-ray diffraction pattern that closely matches the corresponding peaks in the experimental X-ray diffraction pattern.
[0103] For the above structural model, the X-ray diffraction pattern simulated by the DIFFaX program vs. The best fits obtained for the experimental X-ray diffraction patterns of non-stoichiometric β-delithiated layered nickel oxide samples prepared from various non-stoichiometric lithium nickelate precursors are summarized in Table 2.
[0104] Table 2: O1-type stacking and stacking fault fractions of non-stoichiometric β-delithiated layered nickel oxide
[0105]
[0106] The layer fraction of O3-type layer stacking faults is in the range of about 0.02 to about 0.40, the layer fraction of γ-NiOOH-like stacking faults is in the range of about 0.02 to about 0.05, and the layer fraction of the dominant ordered O1 stacking order is in the range of about 0.60 to about 0.95. The structural model successfully explains the inhomogeneous anomalous diffraction peak broadening in the characteristic X-ray powder diffraction pattern of β-delithiated layered nickel oxide samples prepared from non-stoichiometric α-delithiated layered nickel oxide by treating in potassium hydroxide solution.
[0107] Gas Evolution of α- and β-Delithiated Layered Nickel Oxides
[0108] The oxygen evolution rate of the non-stoichiometric β-delithiated layered nickel oxide in contact with an alkaline electrolyte solution was determined using a gas evolution rate analyzer and compared with the oxygen evolution rate of the corresponding non-stoichiometric α-delithiated layered nickel oxide precursor. Table 3 shows the functional relationship between the total gas pressure at 40°C and the storage time. The oxygen evolution rate of the non-stoichiometric β-delithiated layered nickel oxide is significantly less than the oxygen evolution rate of the α-delithiated layered nickel oxide. Specifically, after being stored at 40°C for 80 hours, the total oxygen pressure of the sample of the non-stoichiometric β-delithiated layered nickel oxide is less than 50% of the total oxygen pressure of the corresponding non-stoichiometric α-delithiated layered nickel oxide precursor.
[0109] Table 3: Gas evolution of non-stoichiometric α- and β-layered delithiated nickel oxides
[0110]
[0111] Thus, Table 3 shows that oxygen evolution is advantageously reduced for the non-stoichiometric β-delithiated layered nickel oxide according to the present invention compared to the corresponding non-stoichiometric α-delithiated layered nickel oxide precursor.
[0112] Assembly of AA alkaline primary batteries
[0113] Conventional AA alkaline cells, referred to as Cell A in Table 5 below, were assembled. Cell A included an anode, a cathode, a separator, and an aqueous alkaline electrolyte in a cylindrical housing. The anode contained an anode slurry containing: 4.27 grams of metallic zinc powder; 1.78 grams of an alkaline KOH electrolyte in which about 31 weight percent KOH and 2.0 weight percent ZnO were dissolved in water; 0.026 grams of a polyacrylic acid gelling agent; and 0.023 grams of a corrosion inhibitor. The cathode contained a blend of electrolytic manganese dioxide (EMD), graphite, and an aqueous potassium hydroxide electrolyte solution. The cathode contained a loading of 10.87 grams of EMD, 0.46 grams of Timrex MX-15 graphite, 0.12 grams of Timrex BNB-90 expanded graphite (Imerys Graphite and Carbon, Bodio, Switzerland), and 0.52 grams of an alkaline KOH electrolyte solution. The separator was inserted between the anode and the cathode. The separator was wetted with a pre-shot of about 1.33 grams of alkaline KOH electrolyte solution (about 31 wt. % KOH dissolved in deionized water). The anode, cathode and separator were inserted into a cylindrical casing. The casing was then sealed to complete the cell assembly process. Cell A was then aged at 20° C. for four days and performance tested as described below.
[0114] Experimental AA cells, referred to as Cell B in Table 4 below, were assembled. Cell B included an anode, a cathode, a separator, and an electrolyte in a cylindrical housing. The anode comprised an anode slurry containing: 5.17 grams of metallic zinc powder; 2.17 grams of an alkaline KOH electrolyte in which approximately 27 weight percent KOH and 1.7 weight percent ZnO were dissolved in deionized water; 0.038 grams of a polyacrylic acid gelling agent; and 0.01 grams of a corrosion inhibitor. The cathode comprised a non-stoichiometric blend of β-delithiated layered nickel oxide, graphite, and a potassium hydroxide aqueous electrolyte solution. The cathode comprised a loading of 9.54 grams of β-delithiated layered nickel oxide, 0.78 grams of Timrex MX-15 graphite (Imerys Graphite and Carbon, Bodio, Switzerland), and 0.52 grams of KOH electrolyte solution. The separator was inserted between the anode and the cathode. The separator is wetted with a pre-fill of about 1.00 grams of alkaline KOH electrolyte solution (about 5.5 wt. % KOH dissolved in deionized water). The anode, cathode and separator are inserted into a cylindrical casing. The casing is then sealed to complete the battery assembly process.
[0115] Battery B was then aged at 20°C for four days and performance tested as described below.
[0116] Table 4: Design characteristics of AA battery A and battery B
[0117]
[0118] Performance testing of assembled AA alkaline primary batteries
[0119] Prior to performance testing, the battery was aged at about 20°C for four days. After four days of aging, the open circuit voltage (OCV) of the battery was measured. The OCV of the battery is measured by placing, for example, a voltmeter between the positive and negative terminals of the battery. The measured open circuit voltage (V) of the battery is reported. The OCV test does not consume any capacity from the battery.
[0120] After four days of aging, the short circuit current (SCC) of the battery is measured. The SCC test protocol consists of drawing a constant current of six amperes (Amp) from the battery for 0.1 seconds. The battery voltage is measured and reported at the six ampere current drain. If the battery is completely short-circuited, the measured voltage of the battery will be zero (0) volts. The current at which the battery reaches the short circuit condition is measured by the current vs. The SSC is calculated by extrapolating a line connecting the measured OCV and the measured voltage under drain to the intersection with the x-axis on the x,y graph of voltage. The (x, y) coordinates of the measured OCV are (0Amp, measured OCV). The (x, y) coordinates of the measured voltage under drain are (6Amp, measured load voltage). The SSC test does not deplete a significant amount from the total capacity of the battery due to the extremely short test duration. SSC is calculated by:
[0121] SSC (Amp) = [(OCV•6Amp) / (OCV-load voltage)]
[0122] The performance tests include a discharge performance test which may be referred to as a 30 milliampere (30mA) continuous discharge test. The 30mA continuous discharge test protocol involves discharging the battery at a constant drain current of 30mA until a cutoff voltage of 0.9 volts is reached. The measured capacity of the battery discharged to the cutoff voltage is referred to as the total capacity of the battery. The total capacity of a battery is typically reported in ampere-hours (Ah) and watt-hours (Wh). The 30mA continuous discharge test is considered a low drain continuous discharge test for conventional alkaline AA batteries.
[0123] Performance testing includes a discharge performance test under high rate continuous discharge conditions, which is referred to as a 1 Watt (1W) continuous discharge test. The 1W continuous discharge test protocol involves discharging the battery at a constant power drain of 1 Watt until a cutoff voltage of 0.9 volts is reached. The measured capacity of the battery discharged to the cutoff voltage is typically reported in ampere hours (Ah) and watt hours (Wh). The 1W continuous discharge test is considered a high drain discharge test for conventional alkaline AA batteries.
[0124] Performance testing includes a discharge performance test under a medium rate intermittent discharge state, which is referred to as a 250 milliwatt (250mW) intermittent discharge test. The 250mW intermittent discharge test protocol includes discharging the battery for one hour at a constant power consumption of 250mW. The discharge is then stopped and the battery is allowed to rest for a period of seven hours. The battery is then subjected to additional discharge and rest cycles until a cutoff voltage of 0.9 volts is reached. The measured capacity of the battery is usually reported in ampere hours (Ah) and watt hours (Wh). The 250mW intermittent discharge test is considered a medium consumption intermittent discharge test for conventional alkaline AA batteries.
[0125] The performance tests include a discharge performance test designed to simulate use in a digital camera, which may be referred to as a digital camera test (Digicam). The digital camera test is a pulse test protocol that includes discharging the battery with high and medium power pulse discharge cycles. Each discharge cycle consists of a combination of two discharge states: a 1.5 watt high power pulse lasting 2 seconds, followed by a 650mW medium power pulse lasting 28 seconds. The combination of each discharge state is repeated ten times (i.e., a total of 5 minutes) and the battery is then allowed to rest for a period of fifty-five minutes. The combination of high and medium power discharge pulses and rest time is repeated (i.e., 1 hour / cycle) until a cutoff voltage of 1.05 volts is reached. The number of cycles required to reach the cutoff voltage is reported as "pulse" or "picture". The number of pulses reported consists of the total number of 1.5 watt high power pulses, which corresponds to the total number of discharge cycles. The Digicam discharge test is considered a high rate intermittent discharge test for conventional AA batteries.
[0126] Performance Test Results
[0127] Both battery A and battery B were subjected to OCV, SSC, 30mA continuous, 1W continuous, 250mW intermittent, and Digicam performance testing. Table 5 below summarizes the performance test results. The % difference column of Table 5 includes the percentage difference in performance of battery B relative to battery A. Battery B, which contains non-stoichiometric β-delithiated layered nickel oxide as an electrochemically active cathode material, provides improved overall performance compared to battery A (a typical commercially available conventional alkaline AA battery). The OCV of battery B is higher than that of battery A. The higher OCV of battery B indicates a higher total energy compared to battery A. The OCV of battery B is not too high, so the likelihood of damage is relatively low when battery B is incorporated into an electrical device. The SSC of battery B is significantly higher than that of battery A. The higher SSC of battery B indicates a greater ability to provide a larger discharge current than battery A. Except for the 1W continuous test, the amount of current (Ah) provided by battery B under all discharge tests is greater than that of battery A. The amount of energy (Wh) provided by battery B under all discharge tests is greater than that of battery A. In addition, the number of pulses provided by battery B under the Digicam test is much greater than that of battery A. The results show that battery B generally performs better than battery A for low-rate, medium-rate, and high-rate discharge test conditions.
[0128] Table 5: Performance test results and comparison of battery A and battery B
[0129]
[0130] The dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise specified, each such dimension is intended to refer to the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".
[0131] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patents or applications and any patent applications or patents to which this application claims priority or the benefit, is incorporated herein by reference in its entirety. Citation of any document does not constitute an admission that the document is prior art to any invention disclosed or claimed herein or that it teaches, suggests or discloses any such invention, either alone or in any combination with any other reference or references. In addition, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to the term in this document shall prevail.
[0132] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. It is therefore intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.
Claims
1. A non-stoichiometric β-delithiated layered nickel oxide, the β-delithiated layered nickel oxide comprising a layered crystal structure characterized by a lattice comprising a plurality of NiO2 layers, wherein the lattice comprises an ordered O1-type layer stacking sequence, has at least one O3-type layer stacking fault and at least one γ-NiOOH-like layer stacking fault, and relative to the non-stoichiometric lithium nickelate Li 1-a Ni 1+a O2, wherein 0.02 ≤ a < 0.2, the non-stoichiometric β-delithiated layered nickel oxide having a reduced amount of lithium.
2. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1, wherein the lattice comprises 60% to 95% ordered O1-type layer stacking based on all layers.
3. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the lattice comprises 85% to 95% ordered O1-type layer stacking based on all layers.
4. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the lattice comprises 60% to 85% ordered O1-type layer stacking based on all layers.
5. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the lattice contains 2% to 5% γ-NiOOH-like stacking faults based on all layers.
6. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the lattice contains 2% to 40% O3-type layer stacking faults based on all layers.
7. The non-stoichiometric β-delithiated layered nickel oxide according to claim 6, wherein the lattice comprises 2% to 15% O3-type layer stacking faults based on all layers.
8. The non-stoichiometric β-delithiated layered nickel oxide according to claim 6, wherein the lattice comprises 15% to 40% O3-type layer stacking faults based on all layers.
9. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the NiO2 lattice contains 60% to 95% ordered O1-type layer stacking, 2% to 40% O3-type layer stacking faults and 2% to 5% γ-NiOOH-like layer stacking faults based on all layers.
10. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the β-delithiated layered nickel oxide comprises a chemical formula Li x A y Ni 1+a-z M z O2•nH2O, where x is 0.02 to 0.20; y is 0.03 to 0.20; a is 0.02 to 0.2; z is 0 to 0.2; n is 0 to 1; A comprises an alkali metal, the alkali metal comprising potassium, rubidium, cesium, and any combination thereof; and M includes transition metals, non-transition metals, and any combination thereof.
11. The non-stoichiometric β-delithiated layered nickel oxide of claim 10, wherein the M comprises an alkaline earth metal.
12. The non-stoichiometric β-delithiated layered nickel oxide according to claim 10, wherein z is 0.
13. The non-stoichiometric β-delithiated layered nickel oxide of claim 10, wherein a is between 0.02 and 0.
16.
14. The non-stoichiometric β-delithiated layered nickel oxide of claim 10, wherein x is between 0.3 and 0.
12.
15. The non-stoichiometric β-delithiated layered nickel oxide of claim 10, wherein y is between 0.08 and 0.
13.
16. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the β-delithiated layered nickel oxide has an X-ray diffraction pattern comprising a first peak at 14.9°2θ to 16.0°2θ; a second peak at 21.3°2θ to 22.7°2θ; a third peak at 37.1°2θ to 37.4°2θ; a fourth peak at 43.2°2θ to 44.0°2θ; a fifth peak at 59.6°2θ to 60.6°2θ; a sixth peak at 65.4°2θ to 65.9°2θ; a seventh peak at 10.8° to 12.0°2θ; and an eighth peak at 48.1° to 48.6°2θ.
17. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the γ-NiOOH-like layer stacking fault comprises a P3-type layer stacking order.
18. The non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2, wherein the ordered O1-type layer stacking sequence comprises a stacking order of metal-containing layers, wherein two Ni-containing layers separate each Li-containing layer.
19. An electrochemically active cathode material comprising the non-stoichiometric β-delithiated layered nickel oxide according to claim 1 or 2.
20. A battery, comprising: a cathode comprising a conductive additive and an electrochemically active cathode material, the electrochemically active cathode material comprising the non-stoichiometric β-delithiated layered nickel oxide of claim 1; an anode comprising an electrochemically active anode material comprising zinc, a zinc alloy, and any combination thereof; a separator between the cathode and the anode; and Alkaline aqueous electrolyte.
21. The battery of claim 20, wherein the electrochemically active cathode material comprises the non-stoichiometric β-delithiated layered nickel oxide in an amount of at least 10 wt%, based on the total weight of the electrochemically active cathode material.
22. The battery of claim 20, wherein the electrochemically active cathode material comprises the non-stoichiometric β-delithiated layered nickel oxide in an amount between 10 wt% and 60 wt%, based on the total weight of the electrochemically active cathode material.
23. The battery of claim 20, wherein the electrochemically active cathode material comprises the non-stoichiometric β-delithiated layered nickel oxide in an amount of 50 wt%, based on the total weight of the electrochemically active cathode material.
24. The battery of claim 20, wherein the electrochemically active cathode material comprises the non-stoichiometric β-delithiated layered nickel oxide in an amount of 20 wt%, based on the total weight of the electrochemically active cathode material.
25. The battery of any one of claims 20 to 24, wherein the electrochemically active cathode material further comprises manganese oxide.
26. The battery of claim 25, wherein the manganese oxide is manganese dioxide.
27. The battery of any one of claims 20 to 24, wherein the electrochemically active cathode material further comprises one or more of electrolytic manganese dioxide or chemical manganese dioxide.
28. The battery of any one of claims 20 to 24, wherein the electrochemically active cathode material further comprises one or more of lambda-manganese dioxide or gamma-manganese dioxide.
29. The battery of any one of claims 20 to 24, wherein the remainder of the electrochemically active cathode material comprises manganese oxide.
30. The battery of claim 29, wherein the manganese oxide is manganese dioxide.
31. The battery of any one of claims 20 to 24, wherein the remainder of the electrochemically active cathode material comprises one or more of electrolytic manganese dioxide or chemical manganese dioxide.
32. The battery of any one of claims 20 to 24, wherein the remainder of the electrochemically active cathode material comprises one or more of lambda-manganese dioxide or gamma-manganese dioxide.
33. A method for preparing a cathode material comprising the non-stoichiometric β-delithiated layered nickel oxide of claim 1, the method comprising: Using an oxidant selected from sodium hypochlorite, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium permanganate, potassium permanganate, sodium dichromate or potassium dichromate, a catalyzer having the general formula Li 1-a Ni 1+a-z M z A non-stoichiometric lithium nickelate of O2 is oxidized, wherein 0.02≤a<0.2 and 0≤z<0.2, to obtain a non-stoichiometric α-delithiated layered nickel oxide.
34. A method of making a primary alkaline battery according to claim 20, comprising: By using an oxidizing agent selected from sodium hypochlorite, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium permanganate, potassium permanganate, sodium dichromate or potassium dichromate, the oxidizing agent having the general formula Li 1-a Ni 1+a-z M z A method for oxidizing a non-stoichiometric lithium nickelate of O2, wherein 0.02≤a<0.2 and 0≤z<0.2, to prepare a non-stoichiometric α-delithiated layered nickel oxide.
Citation Information
Patent Citations
Electrically-conductive colorless transparent barium sulfate filler
US5698315A
Method for making multilayer resist structures with thermosetting anti-reflective coatings
US5919598A
Electrically conductive barium sulfate-containing composition and process of producing
US5997775A
Alkaline cell with cathode surface protector
US6514637B2
Cathode material for battery
US7351499B2